Collaboration on the optimal timing of anticoagulation after ischaemic stroke and atrial fibrillation : a systematic review and prospective individual participant data meta-analysis of randomised controlled trials (CATALYST) - Dehbi, Hakim Moulay; Fischer, Urs; Åsberg, Signild; Milling, Truman J.; Abend, Stefanie; Ahmed, Norin; Branca, Mattia; Davis, Lisa A.; Engelter, Stefan T.; Freemantle, Nick; Gattringer, Thomas; Ghukasyan Lakic, Tatevik; et al. (The Lancet, 2025)
Background: The optimal timing of oral anticoagulation for prevention of early ischaemic stroke recurrence in people with acute ischaemic stroke and atrial fibrillation remains uncertain. We aimed to estimate the effects of starting a direct oral anticoagulant (DOAC) early (≤4 days) versus later (≥5 days) after onset of ischaemic stroke. Methods: For this systematic review and meta-analysis we searched the electronic databases PubMed, Cochrane Central Register of Controlled Trials, and Embase for randomised controlled trials published from inception until March 16, 2025. We included clinical trials if they were pre-registered, randomised, investigated clinical outcomes, and included participants with acute ischaemic stroke and atrial fibrillation who were assigned to either early or later initiation (≤4 days vs ≥5 days) of a DOAC in approved doses. The primary outcome was a composite of recurrent ischaemic stroke, symptomatic intracerebral haemorrhage, or unclassified stroke within 30 days of randomisation. Secondary outcomes included components of the primary composite within 30 days and 90 days. We did a one-stage individual patient data meta-analysis with the use of a generalised linear mixed-effects model, accounting for between-trial differences, to generate treatment effects, which are presented as odds ratios (ORs) and 95% CIs. This study is registered with PROSPERO, CRD42024522634. Findings: We identified four eligible trials: TIMING (NCT02961348), ELAN (NCT03148457), OPTIMAS (NCT03759938), and START (NCT03021928). After excluding participants who opted out of data sharing or were not randomly assigned to DOAC initiation within 4 days or at day 5 or later, we included 5441 participants (mean age 77·7 years [SD 10·0], 2472 [45·4%] women, median National Institutes of Health Stroke Scale 5 [IQR 3–10]) in the individual patient data meta-analysis. We obtained primary outcome data for 5429 participants. The primary outcome occurred in 57 (2·1%) of 2683 participants who started DOAC early versus 83 (3·0%) of 2746 participants who started later (OR 0·70, 95% CI 0·50–0·98, p=0·039). Early DOAC reduced the risk of recurrent ischaemic stroke (45 [1·7%] of 2683 vs 70 [2·6%] of 2746, OR 0·66, 0·45–0·96, p=0·029). There was no evidence of an increase in symptomatic intracerebral haemorrhage with early DOAC initiation (10 [0·4%] of 2683 vs 10 [0·4%] of 2746, OR 1·02, 0·43–2·46, p=0·96). Interpretation: For people with acute ischaemic stroke and atrial fibrillation, early DOAC initiation (within 4 days) reduced the risk of the composite outcome of recurrent ischaemic stroke, symptomatic intracerebral haemorrhage, or unclassified stroke within 30 days. These findings support early DOAC initiation in clinical practice. Funding: The CATALYST collaboration was facilitated by a British Heart Foundation grant for OPTIMAS (grant reference number CS/17/6/33361), with support from researchers at the National Institute for Health and Care Research University College London Hospitals Biomedical Research Centre, and a Swiss National Science Foundation grant for ELAN (32003B_197009; 32003B_169975).